A difusão da responsabilidade social : enfoque no certificado de responsabilidade social de Mato Grosso - Baggenstoss, Salli (2009)
In the organizational world, the developments of the actions demonstrate to be increasingly planned, because the reflections can pass both in the internal environment, in society and the environment. It is also evident the spread of social responsibility in organizations, regardless of scope involved. The institutionalization of the social responsibility movement is arising out of entities that provide tools to demonstrate socially responsible actions and their practitioners. However, several studies indicate that the concept of this theme shows divergence in several respects, indicating a process still in elaboration. In these perspectives, this research aims to study the diffusion of social responsibility through the Certificate of Social Responsibility of Mato Grosso. To identify the main components comprised by the speech shown in the certificate, this research is bolstered in the study of Law 7687, in the Committee set up by it, the diagnosis of the participants, in the analysis of social reports required, in presentations at seminars and in interviews and documentary research. The main results show that the Certificate of Social Responsibility of Mato Grosso has a strategic approach and that is supported by the social report tool. As the stakeholders are prioritized employees, the community and the environment. There is no concept laid out by the Joint Commission, to issue involving just limitations. Therefore, it uses the discourse of the participating organizations for the dissemination of the theme. Finally, to receive the certificate, the organization needs to deliver the social report and the declaration. Thus, the institution is considered socially responsible